If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + yr = r + -6g Reorder the terms: 5p + ry = -6g + r Solving 5p + ry = -6g + r Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1ry' to each side of the equation. 5p + ry + -1ry = -6g + r + -1ry Combine like terms: ry + -1ry = 0 5p + 0 = -6g + r + -1ry 5p = -6g + r + -1ry Divide each side by '5'. p = -1.2g + 0.2r + -0.2ry Simplifying p = -1.2g + 0.2r + -0.2ry
| 5y-5=y-12+7y | | (16b-6)-5(3b+3)=-3 | | 5(x-4)+3x-9x=6-(2x-5)+8x | | 0.6x+0.8660y-784.8=0 | | x*x-2=11 | | -5+3v=3v-5 | | 2x+7y=18 | | X-5=-54 | | 9s+12s+4=0 | | -13+5x=4x-7-2 | | 4x-17=4x+16 | | d=4.7+2.8(7.4) | | x*x-2=31 | | 6n+8=6n | | 8y+8=7y-2 | | -8x-x=-16-x | | d=4.7+2.8(12) | | 15+5m=-1+3m | | -3-6v=-v-6v | | =.8(x-25) | | 2.10+12.99b=12.39 | | -9+2k=-2k+7k | | -8a+6a=-2-4a | | 8n-4=-4+8n | | 4cosx+3sinx=y | | 5(X-15)2=75 | | 2a-4+2a=-12+3a | | n+8+2n-4=7+4n-20 | | x+2(-2)=-1 | | 8(4+7n)-6n=332 | | 6=k+7 | | 5x+5-6x=-x+5 |